Overview of Risk Assessment Methodologies for Heavy Metals in the Environment - Raghav Y.; Singh A.; Singh B.P.; Mishra V. (My University, 2025)
The fast expansion of industrialization over the past few decades is associated with a corresponding rise in soil, water, and air pollution. There has been a sharp rise in the frequency of heavy metal contamination, allowing heavy metals to quickly and in large quantities enter the ecosystem and have disastrous impacts. Environmental pollutants, including heavy metals, pose a major risk to human health since they can be inhaled, consumed, or absorbed through the skin. Hence, heavy metal removal is necessary for ecology. This chapter provides a brief overview of the various treatment options for removing metals from the environment. The main objective is to provide relevant information about heavy metals, including where they come from, how they affect the environment, how much soil, air, and water they pollute, and how to calculate the risks associated with coming into contact with them (from sources such as the mining sector, municipal waste, and agricultural wastewater, among others). © 2025 selection and editorial matter Veer Singh, Ashish Kumar, Vishal Mishra and Sachchida Nand Rai; individual chapters, the contributors.